Diet quality, diet motives and nutrition literacy of vegans, vegetarians and semi-vegetarians - Sapna Peruvemba; John Gieng; Susan Chen; Giselle Adriana Pereira Pignotti (Cambridge University Press, 2024)
Abstract Objective: Limited research is available on how motivations to adopt plant-based diets and nutrition literacy influence diet quality. This study assessed diet quality, diet motives and nutrition literacy in vegans, vegetarians and semi-vegetarians and investigated predictors of dietary quality. Design: Cross-sectional study, participants completed an online survey about diet-related motives and nutrition literacy. Dietary intake was assessed with the Diet History Questionnaire III, and diet quality was calculated with the Healthy Eating Index (HEI)-2015. A one-way ANCOVA was used to compare diet quality, nutrition literacy and diet motives among diets. Hierarchical regression analysis was performed to identify significant predictors of diet quality. Setting: Online survey, participants were recruited through paid targeted social media (Facebook/Instagram) advertising. Participants: Adults following a plant-based diet, including 117 (52·5 %) vegans, 51 (22·9 %) vegetarians and 55 (24·6 %) semi-vegetarians. Results: Vegans had higher HEI-2015 scores (80·8 (sd 6·5), P < 0·001) compared to vegetarians (75·1 (sd 9·1)) and semi-vegetarians (76·8 (sd 7·5)). Most participants (74 %) had good nutrition literacy scores. Total nutrition literacy did not differ between groups, but vegans had higher vegetarian nutrition literacy than vegetarians and semi-vegetarians (P < 0·001). Ecological welfare, health and sensory appeal were highly important to all participants. Motives accounted for 12·8 % of the variance in diet quality scores. HEI-2015 scores were positively associated with motives of health and natural content, but negatively associated with weight control motivation (all P < 0·05). Conclusions: Individuals following plant-based dietary patterns have high diet quality and nutrition literacy. Messages valuing intrinsic over extrinsic factors may facilitate healthier dietary adherence in this population.